ANALYSIS OF THE IMPLEMENTATION OF DIFFERENTIATED INSTRUCTION IN MATHEMATICS LEARNING AT SDN 104186 TANJUNG SELAMAT - Jamilah Rambe; Ayu Risnawati; Laura Febriyanti Tambunan; Sezi Oktavia Simarmata; Karyenti Merintan Sani Lahagu; Firman Pangaribuan; Hardi Tambunan (Afore : Jurnal Pendidikan Matematika, 2025)
The purpose of this study is to describe the implementation process of differentiated instruction and the factors that affect the implementation of Mathematics learning using differentiated instruction in the 4th grade. This qualitative research uses descriptive data such as written texts, statements, and behaviors observed in the teaching and learning process. The study was conducted in the odd semester of 2024 at SDN 104186 Tanjung Selamat. The research informants were the teacher and the 4th-grade students. The differentiated instruction in Mathematics implemented in the 4th grade at SDN 104186 Tanjung Selamat had a positive impact on content, process, and product differentiation. Furthermore, the factors influencing the successful implementation of differentiated instruction in 4th-grade Mathematics included effective teaching strategies and active student involvement.